2015
DOI: 10.1016/j.biopsych.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy and Tai Chi Reverse Cellular and Genomic Markers of Inflammation in Late-Life Insomnia: A Randomized Controlled Trial

Abstract: Background Sleep disturbance is associated with activation of systemic and cellular inflammation, as well as pro-inflammatory transcriptional profiles in circulating leukocytes. Whether treatments that target insomnia-related complaints might reverse these markers of inflammation in older adults with insomnia is not known. Methods In this randomized trial, 123 older adults with insomnia were randomly assigned to cognitive behavioral therapy for insomnia (CBT-I), tai chi chih (TCC), or sleep seminar education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
120
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(123 citation statements)
references
References 71 publications
2
120
1
Order By: Relevance
“…For example, cognitive behavioral therapy for insomnia produced large effects on fatigue among HF patients (Redeker et al, 2015), and improved biomarkers of cardiac risk (Carroll et al, 2015; Irwin et al, 2015; Irwin et al, 2014) among a sample of older adults of whom the majority had cardiovascular disorders. Meditation and guided imagery may also be efficacious in improving sleep and sleep-related symptoms among these patients (Kwekkeboom & Bratzke, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cognitive behavioral therapy for insomnia produced large effects on fatigue among HF patients (Redeker et al, 2015), and improved biomarkers of cardiac risk (Carroll et al, 2015; Irwin et al, 2015; Irwin et al, 2014) among a sample of older adults of whom the majority had cardiovascular disorders. Meditation and guided imagery may also be efficacious in improving sleep and sleep-related symptoms among these patients (Kwekkeboom & Bratzke, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Positive changes in immune-related genes (i.e., lower expression of inflammatory cytokines, increases in regulatory genes), implication of the ubiquitin pathway (via pathway analysis) and improvement in depression symptoms were all seen in the improved sleep group, providing insight into the molecular changes that occur with successful insomnia interventions. Further, Irwin and colleagues [95] examined the effects of several insomnia interventions (CBT-I, tai chi) on levels of inflammatory markers in a randomized control trial design using older individuals. Both interventions resulted in positive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Given that both MS and sleep disruption generate pro-inflammatory cytokine profiles, it would be intriguing to assess how co-morbid sleep disturbances affect the cytokine profile, and whether treatment for sleep disorders would be able to modulate the levels of systemic and cellular proinflammatory mediators and the leukocyte expression of pro-inflammatory genes. Interestingly, a recent randomized controlled trial found that CBT and tai chi reversed cellular and genomic markers of inflammation in older adults with insomnia, 51 thus providing an evidence-based molecular framework to understand the potential effects of insomnia treatment on inflammation. Moreover, CBT for insomnia had the additional effect of increasing activity of IFNresponsive transcription factors, 51 consistent with prior findings that CBT increases ex vivo production of IFN.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent randomized controlled trial found that CBT and tai chi reversed cellular and genomic markers of inflammation in older adults with insomnia, 51 thus providing an evidence-based molecular framework to understand the potential effects of insomnia treatment on inflammation. Moreover, CBT for insomnia had the additional effect of increasing activity of IFNresponsive transcription factors, 51 consistent with prior findings that CBT increases ex vivo production of IFN. 52 These findings have potential crucial implications for inflammatory diseases and immuno-mediated CNS disorders, such as MS. Large, prospective, multicenter, cohort studies, using both subjective questionnaire and objective polysomnographic data, are mandatory to address these points.…”
Section: Discussionmentioning
confidence: 99%